Authentic internship journal assessment of industrial training application / Nurulannisa Abdullah ...[et al.] - Abdullah, Nurulannisa; Fadzi, Faizal Haini; Abd Aziz, Nor Erlissa; M Said, Salasiah; Tarsik, Nor Famiza; Md Yatim, Norhidayu (2020)
Authentic internship journal assessment of industrial training program application is a web-based system for students, the industrial training coordinator, the academic supervisor and the industry supervisor. It was created due to the limitations and problems occurred from conventional methods. In paralleled with the change of internet technology the application is developed to manage the industrial training process. The application will become a solution to improve the current process of managing and monitoring the industrial training which were previously being done manually